2007
DOI: 10.1007/s00436-007-0750-1
|View full text |Cite
|
Sign up to set email alerts
|

Arrested development of the myxozoan parasite, Myxobolus cerebralis, in certain populations of mitochondrial 16S lineage III Tubifex tubifex

Abstract: Laboratory populations of Tubifex tubifex from mitochondrial (mt)16S ribosomal DNA (rDNA) lineage III were generated from single cocoons of adult worms releasing the triactinomyxon stages (TAMs) of the myxozoan parasite, Myxobolus cerebralis. Subsequent worm populations from these cocoons, referred to as clonal lines, were tested for susceptibility to infection with the myxospore stages of M. cerebralis. Development and release of TAMs occurred in five clonal lines, while four clonal lines showed immature para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
29
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 32 publications
2
29
0
Order By: Relevance
“…In laboratory experiments using worms collected from California, Montana, Utah, and Argentina, Rasmussen et al (2008) observed higher Lineage III susceptibility in comparison to Lineage I. In comparison, Beauchamp et al (2002) found variation between 2 locations of the Colorado River, Colorado.…”
mentioning
confidence: 91%
See 3 more Smart Citations
“…In laboratory experiments using worms collected from California, Montana, Utah, and Argentina, Rasmussen et al (2008) observed higher Lineage III susceptibility in comparison to Lineage I. In comparison, Beauchamp et al (2002) found variation between 2 locations of the Colorado River, Colorado.…”
mentioning
confidence: 91%
“…There are multiple genetic lineages (I-VI) of T. tubifex (Sturmbauer et al, 1999;Beauchamp et al, 2001;Crottini et al, 2008) that can be distinguished with the use of mitochondrial (16S) and genomic (18S and ITS) DNA sequences. Susceptibility of T. tubifex lineages to infection by the myxospores of M. cerebralis ranges from highly susceptible (Lineage III) and moderately susceptible (Lineage I), to completely resistant (Lineages V and VI; Stevens et al, 2001;Beauchamp et al, 2002;Steinbach et al, 2006;Arsan et al, 2007;Rasmussen et al, 2008). Although much of the work identifying genetic lineages of T. tubifex is based on the mitochondrial 16S rDNA gene, it is unlikely that this gene directly confers resistance to the parasite (Arsan et al, 2007).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…M. cerebralis was detected in Yellowstone Lake in 1998 and over the last decade has posed a growing threat on the declining cutthroat trout population (Koel et al 2005, 2006. The Yellowstone Lake ecosystem is the last stronghold for one of the most ecologically and economically valued inland cutthroat trout populations in North America.We examined Yellowstone cutthroat trout exposed at 4 different times in 3 sites of a Myxobolus cerebralispositive tributary to Yellowstone Lake: Pelican Creek Baxa et al 2008) and abundance of infected T. tubifex to be relatively uniform (J. Alexander, Montana State University, pers. comm.).…”
mentioning
confidence: 99%